Application of Full Mesophilic Anaerobic Effluent Recycling to Very High Gravity Ethanol Fermentation from Cassava - Xu, X.L.; Song, W. (Asian Journal of Chemistry, 2012)
A zero-discharge system composed of ethanol fermentation and biogas fermentation (anaerobic digestion) for cassava-based ethanol production was developed by recycling mesophilic anaerobic effluent. Stillage originated from ethanol fermentation was first treated by the biogas fermentation system and, then, the anaerobic effluent was used as cooking water for the next ethanol fermentation batch. When recycling the anaerobic effluent, the average final ethanol concentration was 14.49 ± 0.29 %, (v/v), which was close to that of the control (14.6 ± 0.1 % (v/v), using tap water for cooking water). This coupled process was confirmed to have stable operation by 10 recycles. This clean technology could thoroughly eliminate the stillage pollution and save about 90 % fresh water used in ethanol fermentation.